Quadratic and cubic non-linearities in a quasi-linear forced system - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 1994)
In [3] the difference between the quadratic non-linearity and the cubic one in a quasi-linear parametrically-excited system has been analyzed. In the present paper, the same question will be examined for a quasi-linear forced system and analogous results as in [3] will be obtained.